2012
DOI: 10.1186/1471-2296-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the coverage of attributes in validated instruments that evaluate primary healthcare from the patient perspective

Abstract: BackgroundPrimary healthcare in developed countries is undergoing important reforms, and these require evaluation strategies to assess how well the population's expectations are being met. Although numerous instruments are available to evaluate primary healthcare (PHC) from the patient perspective, they do not all measure the same range of constructs. To analyze the extent to which important PHC attributes are covered in validated instruments measuring quality of care from the patient perspective.MethodWe syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 18 publications
0
22
0
15
Order By: Relevance
“…Studies have shown that communication, the patient-provider relationship, and preference-based care are important dimensions of person-centred care and SDM [62], and that strategies designed to increase SDM may have a positive impact on patient satisfaction [63] and health outcomes [60,61]. However, other dimensions of person-centred care, such as comprehensiveness of services, cultural sensitivity, and whole-person care, are not well researched [64]. Findings from our study suggest that, along with fostering SDM, IHC services may further support person-centred care by offering a diverse range of TCIM therapies that are culturally appropriate and holistic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that communication, the patient-provider relationship, and preference-based care are important dimensions of person-centred care and SDM [62], and that strategies designed to increase SDM may have a positive impact on patient satisfaction [63] and health outcomes [60,61]. However, other dimensions of person-centred care, such as comprehensiveness of services, cultural sensitivity, and whole-person care, are not well researched [64]. Findings from our study suggest that, along with fostering SDM, IHC services may further support person-centred care by offering a diverse range of TCIM therapies that are culturally appropriate and holistic.…”
Section: Discussionmentioning
confidence: 99%
“…In the Spanish study items such as accessibility and doctor-patient relationship were higher in rural areas, less privileged populations, and among teams involved in the care of elderly [29]. Although PCATooL and other instruments used to evaluate the attributes of PHC do not incorporate the doctor-patient relationship and adoption of evidence-based practices, they included the core attributes [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The strength of primary care system in one country is determined by the degree of development of 4 primary care structure and process dimensions (accessibility, comprehensiveness, continuity, and coordination) as well as the capacity to achieve a high‐quality professional care and cost‐effective health care system …”
Section: Introductionmentioning
confidence: 99%
“…12 The strength of primary care system in one country is determined by the degree of development of 4 primary care structure and process dimensions (accessibility, comprehensiveness, continuity, and coordination) as well as the capacity to achieve a high-quality professional care and cost-effective health care system. [13][14][15][16] To strengthen their primary care delivery systems, many countries have implemented health care reform, a process that included public engagement, political decisions, and significant financial resources. 2 The introduction of PHC reforms in the eastern European countries was particularly challenging because of significant reduction in health care financing, problems in organizational structures, or emigration of physicians to other countries.…”
mentioning
confidence: 99%